TEXT CLASSIFICATION BASED ON SUPPORT VECTOR MACHINE - Lê, Thị Minh Nguyện (Trường Đại học Đà Lạt, 2023)
The development of the Internet has increased the need for daily online information storage. Finding the correct information that we are interested in takes a lot of time, so the use of techniques for organizing and processing text data are needed. These techniques are called text classification or text categorization. There are many methods of text classification, but for this paper we study and apply the Support Vector Machine (SVM) method and compare its effect with the Naïve Bayes probability method. In addition, before implementing text classification, we performed preprocessing steps on the training set by extracting keywords with dimensional reduction techniques to reduce the time needed in the classification process.